2001
DOI: 10.1007/bf03392970
|View full text |Cite
|
Sign up to set email alerts
|

The Functional Analysis of Problematic Verbal behavior

Abstract: This study describes procedures and outcomes in a functional analysis of problem behavior of 2 public school students. For a 13-year-old honors student, bizarre tacts (labeled as psychotic speech by school staff) were maintained by attention. For a 15-year-old with autism, the functional analysis revealed that perseverative mands for toileting were controlled by attention; mands for edible items were controlled by access to any food item; and mands for nonedible items were maintained by access to the specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Verbal responses that concern or trouble listeners are variously labeled as perseverative (i.e., repetitive or stereotyped words or phases), delusional (obviously false statements), psychotic (words or phrases unrelated to ongoing environmental events), hallucinatory (verbal responses to unobservable stimuli), and echolalic (persistent repetitions of the words or phrases of others) (Ewing, Magee, & Ellis, 2002;Wilder, Masuda, O'Connor, & Baham, 2001). These behavior problems are common in developmentally disabled and psychiatric populations, and such bizarre or aberrant speech is sometimes considered to be symptomatic of an underlying mental illness, such as schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Verbal responses that concern or trouble listeners are variously labeled as perseverative (i.e., repetitive or stereotyped words or phases), delusional (obviously false statements), psychotic (words or phrases unrelated to ongoing environmental events), hallucinatory (verbal responses to unobservable stimuli), and echolalic (persistent repetitions of the words or phrases of others) (Ewing, Magee, & Ellis, 2002;Wilder, Masuda, O'Connor, & Baham, 2001). These behavior problems are common in developmentally disabled and psychiatric populations, and such bizarre or aberrant speech is sometimes considered to be symptomatic of an underlying mental illness, such as schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…Aberrant or bizarre talk is a behavioral problem not often focused on in the functional literature, even though there have been some important contributions (DeLeon, Arnold, Rodriguez-Catter, & Uy, 2003;Dixon, Benedict, & Larson, 2001;Dunlap, Kern-Dunlap, Clarke, & Robbins, 1991;Durand & Crimmins, 1987;Ewing et al, 2002;Lancaster et al, 2004;Mace & Lalli, 1991;Mace et al, 1988;Wilder et al, 2001). We wished to contribute to the literature by using a descriptive analysis to reveal functional relations.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that positive social reinforcement in the form of attention, and negative reinforcement, in the form of escape from aversive situations, may also serve as maintaining consequences for repetitive behaviors (e.g., Durand & Carr, 1987). Studies of verbal problem behavior (e.g., bizarre vocalizations, echolalia, perseverative speech) have identified positive social reinforcement (i.e., attention; e.g., Rehfeldt & Chambers, 2003), negative reinforcement (i.e., escape from demands; e.g., Pace, Iwata, Cowdrey, Andree, & McIntyre, 1993), access to tangible items (e.g., Ewing, Magee, & Ellis, 2002); and nonsocial functions (i.e., automatic reinforcement; e.g., Ahearn, Clark, MacDonald, & Chung, 2007) as maintaining them. Studies have also shown that repetitive behavior displayed by individuals with autism can be used to reinforce alternative low-rate behaviors (Charlop, Kurtz, & Casey, 1990;Hung, 1978;Sugai &White, 1986;Wolery, Kirk, & Gast, 1985) suggesting that such behavior can be potent reinforcers.…”
Section: Perseverative Conversation Explained From a Behavioral Perspmentioning
confidence: 99%
“…Within behavioral psychology, use of the term verbal perseveration has been associated with several meanings. For example, it has been used to mean verbal utterances sharing 50% of the "lexical items" as previous utterances (Reichle, Brubakken, & Tetreault, 1976), high-rate contextually inappropriate verbalizations, including repetitive requests for items and activities (Ewing et al, 2002), and single words or phrases about a narrow topic (Kostinas, Scandlen, & Luiselli, 2001). Other studies (e.g., Dixon, Benedict, & Larson, 2001;Wilder, Masuda, O'Connor, & Baham, 2001) have described target behaviors similar to one or more of the above examples, but termed them something else (e.g., inappropriate verbal behavior, bizarre vocalizations).…”
Section: Perseveration and Circumscribed Interests In Conversationmentioning
confidence: 99%
“…Numerous studies conducted in applied behavior analysis have shown that the stereotyped and often bizarre verbal responses exhibited by persons with autism, schizophrenia or psychotic symptoms are, like many other conduct disorders, acquired and maintained either by contingent social attention or by escape from aversive situations (Deleon, Arnold, Rodriguez-Catter, & Uy, 2003;Dixon, Benedict, & Larson, 2001;Durand & Crimmins, 1987;Ewing, Magee, & Ellis, 2002;Mace & Lalli, 1991;Rehfeldt & Chambers, 2003;Wilder, Masuda, O'Connor, & Baham, 2001;Wong, 1996). It is also probable that in some cases these verbalizations have an intrinsic reinforcing power which maintains them automatically (Lovaas, Varni, Koegel, & Lorsch, 1977;Wong et al, 1987).…”
Section: Introductionmentioning
confidence: 97%